PERUBAHAN SOSIAL MASYARAKAT PETANI TERHADAP ALIH FUNGSI LAHAN PERTANIAN DI DESA MARGA AGUNG, KECAMATAN JATI AGUNG, LAMPUNG SELATAN - Siti Mariyani; Ekalia Yusiana (Lampung University, 2023)
This study aims to determine factors causing land conversion in Marga Agung Village and social change of the farming community in Marga Agung Village towards the conversion of agricultural land. This research is a survey research using a qualitative approach which is analyzed descriptively. The data collection method was carried out using in-depth interviews with nine informants who were selected purposively. The research was conducted in Marga Agung Village, Jati Agung District, South Lampung, as a consideration that the majority of farmers in Marga Agung Village is rain-fed farmers and come from the village bedol transmigration program which has experienced the conversion of agricultural land. The results of the study indicated that the factors causing land conversion in Marga Agung Village are internal factors and external factors. The internal factor of the farmer households is in the form of the socio-economic conditions of the farmer household such as household needs which cannot be fulfilled by the income of the farmer households. The external factors of farmers selling agricultural land are the price of land which is increasing every year, the strategic location of the land also increases the selling price of the land and there is an increase in the population coming from outside the Marga Agung Village area. Key words: farmer, land conversion, social change.